Examining Value Change in MOOCs in the Scope of Connectivism and Open Educational Resources Movement - Ozturk, Hayriye Tugba (International Review of Research in Open and Distributed Learning, 2015)
Massive Open Online Courses (MOOCs) came to prominence with Open Educational Resources Movement (OERM). It was based upon the idea of libre in removal of some permission barriers and gratis in removing the price barrier (Suber, 2008) in learning resources. In line with the theoretical underpinnings of OERM, MOOCs embody primary characteristics of connectivist pedagogy which are autonomy, diversity, openness, and community participation. However, in time, moving away from its original philosophical and pedagogical values, new variations of MOOCs have emerged and new MOOCs have become more market oriented and are aligned with instructivist, cognitive, and behaviourist pedagogy. In an attempt to empirically examine the change in underlying values of the MOOCs, a survey method was employed by using a Connectivist Learning Environment Assessment Tool which was developed in the scope of this research. The tool could be useful for formulating and justifying a conceptual framework that enables us to reify the connectivist pedagogy and assess connectivist underpinnings of a learning environment including MOOCs. This research aims to contribute to MOOC studies against the background of previous knowledge from the Open Education and Connectivist fields.